2014
DOI: 10.1353/mos.2014.0042
|View full text |Cite
|
Sign up to set email alerts
|

(Not) Lost in the Margins: Gender and Identity in Graphic Texts

Abstract: Female graphic writers have been under-represented in scholarship about the emerging field. This essay argues that Marjane Satrapi, Alison Bechdel, and Rutu Modan use the genre to push in from the (literal and metaphorical) margins to challenge literary, sexual, and nationalist norms through both their storylines and their illustrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Still, most importantly, it also tries to elevate the role of women and empower them through the use of graphic novels as a pedagogical tool in ESL classrooms. A number of studies are now looking into gender (mis) representations found in the narratives of graphic materials and have discovered both disturbing and hopeful observations when it comes to understanding gender or gender roles in society (e.g., Allison, 2014;Nayar, 2017), which findings and concerns are also shared by this study. By identifying and revealing what can be regarded as visual misrepresentations of or discrimination against women, it seeks to create awareness on these pertinent issues on both teachers and students in Malaysian contexts.…”
Section: Discussionmentioning
confidence: 66%
“…Still, most importantly, it also tries to elevate the role of women and empower them through the use of graphic novels as a pedagogical tool in ESL classrooms. A number of studies are now looking into gender (mis) representations found in the narratives of graphic materials and have discovered both disturbing and hopeful observations when it comes to understanding gender or gender roles in society (e.g., Allison, 2014;Nayar, 2017), which findings and concerns are also shared by this study. By identifying and revealing what can be regarded as visual misrepresentations of or discrimination against women, it seeks to create awareness on these pertinent issues on both teachers and students in Malaysian contexts.…”
Section: Discussionmentioning
confidence: 66%
“…Women’s life writing in graphic form allows for the articulation/inscribing of multiple selves, permits the exploration of typically private subjects like the body, sexual trauma and taboo, vehemently makes visible what otherwise ought not to be, or cannot be, seen and instantiates an eversion of states of interiority (Allison, 2014; Basu, 2007; Chute, 2008; Nayar, 2015; Squier, 2008). Hillary Chute has argued for the appeal of the graphic form in service of a feminist methodology (Chute, 2008, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The centrality of the medium in representations of gender-in-crisis, gender-and-agency, gender-and-human-rights, gender-and-representation has attracted attention from commentators (Allison, 2014; Chute, 2010; Mandaville, 2009). Their writings point to the flexibility of language, both verbal and visual, in the form that enables the staging of the gender theme.…”
mentioning
confidence: 99%